31.0k views
0 votes
Show work help 1-6.

Show work help 1-6.-example-1
User YonahW
by
6.7k points

1 Answer

5 votes

Explanation:

1.

there are two given value for x so the value of y will change accordingly

for x = -1 ➡ y + 5 × -1 = 6 ➡ y = 11

and for x = 0 ➡ y + 5 × 0 = 6 ➡ y = 6

2.

for x = -3 ➡ 8×-3 -4y = -12 ➡ y = -3

for x=-1 ➡ 8×-1 -4y = -12 ➡ y = 1

3.

for x = -3 ➡ -3y = 2× -3 -9 ➡ y = 5

for x = 0 ➡ -3y = 2×0-9 ➡ y = 3

4.

for x = 1 ➡ 5×1 = -y + 6 ➡ y = 1

for x = 2 ➡ 5×2 = -y + 6 ➡ y = -4

5.

for x = -4 ➡ 6y = (-4)×(-3)+12 ➡ y = 4

for x = -2 ➡ 6y = (-2)×(-3)+12 ➡ y = 3

6.

for x = -2 ➡ -5y + 10×(-2) = 5➡ y = -5

for x = 0 ➡ -5y + 10×0 = 5➡ y = -1

User MindFold
by
6.2k points